Partnerships for Evergreen Agriculture in Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Dennis Garrity, Drylands Ambassador, World Agroforestry Centre (ICRAF) talks about developing partnerships for Evergreen Agriculture in Africa. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/